The early medieval village of Morawy: a grave field from the 11th century - Danielewski, Marcin (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
This article deals with the issues of an 11th century grave field in Morawy village in Kuyavia. In the first Piast times, the area was an integral part of the dynasty’s dominion. Discovered in the 1930s, the grave field is of great importance from the point of view of considerations of ethnically foreign settlements in Poland.